Preparing Excitable Cardiac Papillary Muscle and Cardiac Slices for Functional Analyses - Palmer, Bradley M.; Bell, Stephen P. (Frontiers in Physiology, 2022)
While the reductionist approach has been fruitful in understanding the molecular basis of muscle function, intact excitable muscle preparations are still important as experimental model systems. We present here methods that are useful for preparing cardiac papillary muscle and cardiac slices, which represent macroscopic experimental model systems with fully intact intercellular and intracellular structures. The maintenance of these in vivo structures for experimentation in vitro have made these model systems especially useful for testing the functional effects of protein mutations and of pharmaceutical candidates. We provide solutions recipes for dissection and recording, instructions for removing and preparing the cardiac papillary muscles, as well as instructions for preparing cardiac slices. These instructions are suitable for beginning experimentalists but may be useful for veteran muscle physiologists hoping to reacquaint themselves with macroscopic function analyses.